Phytochemical, purification and spectral analysis of compounds from root tuber extract of Aparagus racemosus (Willd). (2021) - Suja, S.; Sivakala, S.
Abstract: Asparagus racemosus the queen of herbs is an important medicinal plant regarded as a ayurvedic rasayana, a plant drug which prevent ageing, increase longevity, impart immunity, improve mental function, vigour and add vitality to the body. It recommended for female health in habitual abortions, weakness of the uterus, excessive bleeding during menstruation etc. Based on the fragmentary information an investigation of the crude methanolic extract of the roots for the presence of bioactive components was done adopting Harborne method. The phytochemical screening revealed the presence of chemical constituents such as alkaloids, flavonoids, steroidal saponins and carbohydrates. The TLC profiling of the methanolic extract showed four active spots for flavonoids, saponins and other secondary metabolites. The spectral analysis using Gas Chromatography-Mass Spectrometry identified about 13 major and 5 minor active constituents. Identification of steroidal sapogenin from the GC/MS spectra was the highlight of this present study. Diosgenin, the steroidal sapogenin is the precursor for the semisynthesis of progesterone.